2008
DOI: 10.1292/jvms.70.571
|View full text |Cite
|
Sign up to set email alerts
|

Genoepidemiological Evaluation of Bovine viral diarrhea virus 2 Species Based on Secondary Structures in the 5' Untranslated Region

Abstract: ABSTRACT. Bovine viral diarrhea virus 2 (BVDV-2) strains demonstrated in cattle, sheep, and adventitious contaminants of biological products have been evaluated by the palindromic nucleotide substitutions (PNS) method at the three variable loci (V1, V2 and V3) in the 5' untranslated region (UTR), to determine their taxonomical status. Variation in conserved genomic sequences was used as parameter for epidemiological evaluation of the species in relation with geographical distribution, animal host and virulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
0
27
0
3
Order By: Relevance
“…Two BVDV genotypes (type 1 and 2) are recognized according to serological and genetic relatedness [7]. The BVDV isolates circulating in the world are heterogeneous: BVDV genotype 1 (BVDV-1) is subdivided into a minimum of 12 sub-genotypes (BVDV1a, b, c.…l), whereas BVDV genotype 2 (BVDV-2) is classified into 4 subtypes, 2a-2d [8, 9]. The BVDV can also be divided into cytopathic and non-cytopathic biotypes (cpBVDV and ncpBVDV, respectively), based on their lytic effects on infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…Two BVDV genotypes (type 1 and 2) are recognized according to serological and genetic relatedness [7]. The BVDV isolates circulating in the world are heterogeneous: BVDV genotype 1 (BVDV-1) is subdivided into a minimum of 12 sub-genotypes (BVDV1a, b, c.…l), whereas BVDV genotype 2 (BVDV-2) is classified into 4 subtypes, 2a-2d [8, 9]. The BVDV can also be divided into cytopathic and non-cytopathic biotypes (cpBVDV and ncpBVDV, respectively), based on their lytic effects on infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of divergence between single strain sequences or genetic groups was obtained easily by comparing base pairing from aligned secondary structure sequences. This provided clear information such as the level of heterogeneity within a species, the genetic distance between species in terms of variation of base pairs in the secondary structure, or helping for the characterization and clustering of specific strains (Table 4) group BVDV-2A, constituting a separate genotype in addition to the four genotypes, BVDV-2a, BVDV2b, BVDV-2c, and BVDV-2d previously described (Giangaspero et al, 2008a). In the present study, the…”
mentioning
confidence: 53%
“…Hyper-virulent strains 890 and CD-87 have been previously included in BVDV species in a separate cluster [55,57]. Correlation between clinical features related with isolation of BVDV-2 strains with genetic variation indicated that genotype 2a; subgenotype 1, variants 4 and 5 were related with hemorrhagic syndrome [53]. The hemorrhagic syndrome has been reported also in European cattle [24,36,[58][59][60].…”
Section: Introductionmentioning
confidence: 93%
“…Chronologically, the species emerged in North America in 1978, spreading in UK and Japan, continental Europe, South America and New Zealand. Correlation between clinical features related with isolation of BVDV-2 strains and genetic variation indicated specific genomic variants related with hemorrhagic syndrome [53]. The PNS procedure was useful also for the evaluation of the probable common origin of the BVDV-3 species spreading via commercialization of FBS batches from South America [35].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation